Siponimod (BAF312) penetrates, distributes, and acts in the central nervous system: Preclinical insights. Issue 4 (October 2021) - Bigaud, Marc; Rudolph, Bettina; Briard, Emmanuelle; Beerli, Christian; Hofmann, Andreas; Hermes, Erwin; Muellershausen, Florian; Schubart, Anna; Gardin, Anne
Background: Siponimod (BAF312), a selective S1P1 /S1P5 agonist, reduces disability progression in secondary progressive MS. Recent observations suggest it could act via S1P1 /S1P5 -dependent anti-inflammatory and pro-myelination effects on CNS-resident cells. Objective: Generate preclinical evidence confirming siponimod's CNS penetration and activity. Methods: Siponimod's CNS penetration and distribution was explored in rodents and non-human primates (NHPs) using: Liquid Chromatography coupled to tandem Mass Spectrometry (LC-MS/MS), quantitative whole-body autoradiography (QWBA) using 14 C-radiolabeled siponimod or non-invasive single-photon emission CT (SPECT) with a validated 123 I-radiolabeled siponimod analog. Functional CNS activity was investigated by S1P1 receptor quantification in brain homogenates. Results: In mice/rats, siponimod treatments achieved dose-dependent efficacy and dose-proportional increase in drug blood levels, with mean brain/blood drug-exposure ratio (Brain/Blood DER) of 6–7. Efficacy in rat brain tissues was revealed by a dose-dependent reduction in brain S1P1 levels. QWBA distribution analysis in rats indicated that [ 14 C]siponimod related radioactivity could readily penetrate CNS, with particularly high uptakes in white matter of cerebellum, corpus callosum, and medulla oblongata versus lower exposures in other areas such as olfactory bulb. SPECT monitoring in NHPs revealed CNS distribution with abrain/blood DER of ∼6, as in rodents. Conclusion: Findings demonstrate siponimod's CNS penetration and distribution across species, with high translational potential to human.